Generation Y learning in the 21st century: integration of virtual worlds and cloud computing services - Chang, Vanessa; Guetl, Christian (AACE, 2010)
In recent time, learning and teaching strategies have been significantly influenced by technological innovation. Latest technologies have altered how information is presented and how students interact with that information. Not only would educators have to cope with new technologies, they also have to deal with a new generation of learners: learners of different learning attitudes and styles. An understanding of the characteristics, learning behaviour, habits and styles of Generaion Y is explored in this paper. As a result, this paper also gives an overview to four technologies that can support this specific group in learning activities and consequently educators can embed in their curriculum: (a) mobile technology, (b) games technology; (c) 3D virtual worlds and (d) cloud computing. This paper will present an example of how virtual worlds and cloud computing are used in a course that incorporated experiential and student-centered learning practices. The challenges and the benefits of the approaches as well as some implicatins for the future of education will conclude the paper.